2015
DOI: 10.5152/dir.2014.14094
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of real-time elastography in diagnosis of polycystic ovary syndrome

Abstract: ABDOMINAL IMAGINGORIGINAL ARTICLE PURPOSE We aimed to assess the feasibility and reproducibility of real-time elastography (RTE) for displaying the effects of morphological changes in the ovary in polycystic ovary syndrome (PCOS). METHODSForty-eight patients diagnosed with PCOS and 48 healthy women were enrolled in the study. Ultrasonography and RTE were performed on the 3 rd day of the menstrual cycle. Evaluations were performed independently by two radiologists. Ovarian volume, number of follicles, elasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
1
13
4
Order By: Relevance
“…Although a slight correlation of SWE with BMI and ovarian volume was detected, clinical relevance of SWE to determine PCOS was not obvious given the results of our study. Our results are in contrast with Ciraci et al study [17], the authors demonstrating high stiffness of the ovarian stroma when PCOS is present. However, Ciraci et al [17] used SE which is highly subjective and lacks quantifiable parametric values.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although a slight correlation of SWE with BMI and ovarian volume was detected, clinical relevance of SWE to determine PCOS was not obvious given the results of our study. Our results are in contrast with Ciraci et al study [17], the authors demonstrating high stiffness of the ovarian stroma when PCOS is present. However, Ciraci et al [17] used SE which is highly subjective and lacks quantifiable parametric values.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in contrast with Ciraci et al study [17], the authors demonstrating high stiffness of the ovarian stroma when PCOS is present. However, Ciraci et al [17] used SE which is highly subjective and lacks quantifiable parametric values. We used SWE to evaluate elasticity of ovarian stroma, a method in which the elasticity is objectively calculated by the regular software of US device [15].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These elastographic techniques are strain elastography (SE), which compresses the tissues axially, and shear wave elastography (SWE), which uses waves that are generated by transducers and interact with the tissue . In some studies, it has been reported that there is a connection between the tissue elasticity and histologic features . The purpose of this work is to describe the optic nerve's elastic characteristics in patients with migraine using SE and SWE and to compare the findings to those of healthy participants to establish whether these elastic characteristics can be used to assist in the diagnosis of optic nerve involvement in patients with migraine.…”
mentioning
confidence: 99%
“…[14][15][16][17] In some studies, it has been reported that there is a connection between the tissue elasticity and histologic features. [14][15][16][17][18] The purpose of this work is to describe the optic nerve's elastic characteristics in patients with migraine using SE and SWE and to compare the findings to those of healthy participants to establish whether these elastic characteristics can be used to assist in the diagnosis of optic nerve involvement in patients with migraine.…”
mentioning
confidence: 99%